2012
DOI: 10.2355/isijinternational.52.1544
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Viscometer Based on Rotating Crucible Method and Viscosity Measurement of SiO2^|^ndash;CaO^|^ndash;CaF2 System

Abstract: The development of a new viscometer based on rotating crucible method and the viscosity measurement of SiO2-CaO-CaF2 system were carried out. The viscometer was hermetically closed, and the atmosphere around the melts was highly controllable. In the viscosity measurement, an inner cylinder made of graphite was immersed into the melts in a graphite crucible under Ar at elevated temperatures (1 467-1 782 K). The torque given to the inner cylinder by rotating the crucible was measured by means of a supersensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…In order to meet these requirements, it is necessary to consider and quantify the effect of fluorspar (CaF 2 ) addition on the viscosity of MnO-containing slags at high temperatures, because the CaF 2 is well known to decrease the viscosity of silicate melts. [3][4][5][6][7][8][9][10][11][12]15,19,20,24) The experimental study of the effect of CaF 2 on the viscosity of various silicate melts has been investigated by several researchers for CaO-SiO 2 (-MgO)-CaF 2 , [3][4][5][10][11][12]24) FeO(-CaO)-SiO 2 -CaF 2 , [6][7][8] CaOSiO 2 -Na 2 O-Li 2 O-CaF 2 , 19) and CaO-Al 2 O 3 -SiO 2 -MgO-CaF 2 systems. 20) From the above studies, the viscosity itself and the activation energy of Newtonian flow of silicate melts generally decrease with increasing content of CaF 2 due to depolymerization reactions of silicate networks, indicating that the addition of CaF 2 is more effective in higher silica content region.…”
Section: Introductionmentioning
confidence: 99%
“…In order to meet these requirements, it is necessary to consider and quantify the effect of fluorspar (CaF 2 ) addition on the viscosity of MnO-containing slags at high temperatures, because the CaF 2 is well known to decrease the viscosity of silicate melts. [3][4][5][6][7][8][9][10][11][12]15,19,20,24) The experimental study of the effect of CaF 2 on the viscosity of various silicate melts has been investigated by several researchers for CaO-SiO 2 (-MgO)-CaF 2 , [3][4][5][10][11][12]24) FeO(-CaO)-SiO 2 -CaF 2 , [6][7][8] CaOSiO 2 -Na 2 O-Li 2 O-CaF 2 , 19) and CaO-Al 2 O 3 -SiO 2 -MgO-CaF 2 systems. 20) From the above studies, the viscosity itself and the activation energy of Newtonian flow of silicate melts generally decrease with increasing content of CaF 2 due to depolymerization reactions of silicate networks, indicating that the addition of CaF 2 is more effective in higher silica content region.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] However, it is difficult to determine a precise low torque due to the mechanical friction inside the viscometer. 17) Viscometers of this type consist of two concentric cylinders (a bob and a crucible) and the viscosity is determined from the calculations of the torque of bob at constant or different rotations. A few other studies were reported to use the different types of viscometers such as the rotation crucible viscometer and the oscillating plate method.…”
Section: Introductionmentioning
confidence: 99%
“…A few other studies were reported to use the different types of viscometers such as the rotation crucible viscometer and the oscillating plate method. [17][18][19][20] The concentric cylinder method was primary used for the determination of slag viscosity. It…”
Section: Introductionmentioning
confidence: 99%
“…$ η values mean the viscosity of the slags at 1823 K. For the CaO-SiO2-Al2O3 and the CaO-SiO2-MgO system, the temperature dependences of the viscosity, which were reported by the group of Machin et al [23][24][25] , are extrapolated and listed in this Table. (Viscosity data of the 30 mass%CaO-60 mass%SiO2-10 mass%Al2O3 (or MgO) are used instead of those of the 32 mass%CaO-58 mass%SiO2-10 mass%Al2O3 (or MgO) slags in this Table.) The viscosities of the CaO-SiO2-CaF2 system were determined by interpolation of the data reported by Takeda et al 26) . * Density of the bulk slag, ρb, was calculated based on the additivity rule using the reported partial molar volume values determined at 1773 K 27) .…”
Section: 実験方法mentioning
confidence: 99%